Preparation, Release Pattern and Antibacterial Activities of Chitosan-Silver Nanocomposite Films - O. I., Sonde; S.O., Ogungbesan; J.O., Olaniyan; A.R., Oloyede; M. A., Idowu; T.A., Afolabi; O., Adetunji; E. O., Dare (Covenant Journal of Physical and Life Sciences, 2017)
The present study examined the preparation of chitosan-silver nanocomposite films as carriers for silver release pattern. Chitosan a biopolymer having immense structural possibilities for chemical and mechanical modifications to generate novel properties, functions and applications. Chitosan–silver nanocomposite films has been synthesised by reduction method, which is a simple and inexpensive method. The chitosan-silver nanocomposite films was characterized in terms of its surface plasmon resonance and crystalline structure by using UV-Visible spectroscopy, X-ray diffraction, Fourier transform infrared and Scanning electron microscope. Swelling and release studies were carried out on crosslinked and un-crosslinked nanocomposite films. Antibacterial activities of chitosan-silver nanocomposite films were investigated on some pathogens: Staphylococcus aureus, Shigella dysenteriae, Escherichia coli, Salmonella typhii and Klebsiella pneumonia using agar well diffusion method. crosslinked chitosan-silver nanocomposite demonstrated a slower release pattern relative to un-crosslinked chitosan-silver nanocomposite. The crosslinked and un-crosslinked nanocomposite became dislodged and completely released at 120 minutes and 90 minutes respectively. The results of the antibacterial activities revealed that the cross-linked chitosan-silver nanocomposite films has higher antibacterial properties than un-crosslinked chitosan-silver nanocomposite films. This study provides nanocomposite films potentially useful for delivery system.